ANALISIS PENERAPAN MEDITASI SAMATHA BHAVANA DI MASA COVID-19 TERHADAP KESEHATAN MENTAL UMAT BUDDHA VIHARA DHARMA LOKA PEKANBARU - Hadion Wijoyo; Julia Surya (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The COVID-19 outbreak made many public activities shift with the main activity center being at home. This situation is a new reality that is also experienced by the world of education. Like it or not, like it or not, all parties starting from the teacher, parents, and students must be prepared to live a new life (new normal) through a learning approach using information technology and electronic media so that the teaching process can take place properly. In parents the condition can be more severe, because not only must be able to concentrate on work but also must act as a teacher for children who study at home. So the stressors can be multiplied and parents are very much asked to be able to handle this situation well. Meditation in the Buddhist tradition comes from the word bhavana which means culture or mental development. Mental development referred to here is broad mental development.Keywords: Samatha Meditation, Covid-19, Mental Health